2018
DOI: 10.1200/jco.2017.75.3228
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Versus Stereotactic Body Radiotherapy for Localized Hepatocellular Carcinoma in Nonsurgically Managed Patients: Analysis of the National Cancer Database

Abstract: Purpose Data that guide selection of optimal local ablative therapy for the management localized hepatocellular carcinoma (HCC) are lacking. Because there are limited prospective comparative data for these treatment modalities, we aimed to compare the effectiveness of radiofrequency ablation (RFA) versus stereotactic body radiotherapy (SBRT) by using the National Cancer Database. Methods We conducted an observational study to compare the effectiveness of RFA versus SBRT in nonsurgically managed patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
146
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 32 publications
3
146
2
3
Order By: Relevance
“…One and two‐year survival was similar between the two groups, which is consistent with the findings of our analysis . A more recent study using the National Cancer Database of nearly 4000 patients who received RFA and SBRT for HCC showed that RFA patients had a superior 5‐year survival in a propensity‐matched cohort . While the conclusions of this study differ from our findings, there are several reasons this may be the case.…”
Section: Discussionsupporting
confidence: 90%
“…One and two‐year survival was similar between the two groups, which is consistent with the findings of our analysis . A more recent study using the National Cancer Database of nearly 4000 patients who received RFA and SBRT for HCC showed that RFA patients had a superior 5‐year survival in a propensity‐matched cohort . While the conclusions of this study differ from our findings, there are several reasons this may be the case.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have also compared the outcomes of RFA and SBRT using PSM . However, these studies had limitations.…”
Section: Discussioncontrasting
confidence: 69%
“…Neither of the previous PSM studies considered liver function . In patients with HCC, unlike most solid tumors, there are two life‐threatening conditions: cancer and cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, chemotherapy and/or radiotherapy have been increasingly used over the past decade in the US with only limited survival benefit . In turn, local ablative techniques, such as the RFA have recently demonstrated promising results in localized ICC, especially intermediate (3‐5 cm) and small (<3 cm) ICCs; yet robust evidence regarding the optimal nonsurgical management of patients with ICC is still lacking . The current study was important because we demonstrated that RFA was associated with a 54% lower mortality risk compared with chemo‐ or radio‐therapy among patients with early stage (stage I/II) unresectable ICC.…”
Section: Discussionmentioning
confidence: 79%